Studi Farmakognosi tumbuhan Gynura procumbens (LOUR) MERR=Pbarmacognostic study of Gynura procumbens (Lour) Merr - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
A research on the morphology, leaf anatomy, extraction, isolation and identification of the flavonoids of Gynura procumbens (Lour) Merr has been done. Flavonoid extraction was done by boiling the powdered leaves with hot water, evaporating of the water extract and dissolving the residue in 95% aethanol. The flavonoid was isolated by column chromatography using cellulose as the stationary phase, and aethanol-water (1:4) v/v as the mobile phase, followed by preparative thin layer chromatography with cellulose as stationary phase and as the mobile phase, a mixture of butanol- toluene-acetic acid-water (2:2:1:5) v/v. Further purification were done by preparative thin-layer chromatography, with 30% acetic acid and BAW as mobile phase. The isolated flavonoids and the hydrolyzed products were analyzed by using UV spectrophotometer with or without the addition of reagents to form the salt and complex. The morphological data shows that Gynura procumbens has a specific character: decumbent and has orange yellow flowers, which will change to whitish violet and then reddish-brown. Anatomical data does not show any specificity. Four flavonoids had been isolated, and the UV spectra showed that the first one was hypothesized as flavon with OH on C7, C3', C4', and on C5 an alkyl, alkoxy or H. The third one was hypothesized as flavonol with OH on Cs, C7 and C4,' on C3 was glucose, on C3', was an alkoxy or H. The fourth flavonoid was hypothesized a flavonol with OH on C5, C3', Cr, on C3 was glucose, on C7 was an alkoxy.